"Reciprocal" depression of the ST segment in acute myocardial infarction. Issue 6393 (3rd September 1983) - Jennings, K; Reid, D S; Julian, D G
Abstract : In acute myocardial infarction depression of the ST segment in leads distant from those showing ST elevation has been considered to be "reciprocal" but might reflect local ischaemia. To examine this possibility 103 consecutive patients who underwent exercise testing early after myocardial infarction were reviewed. Treadmill exercise testing was performed a mean of 12 (range 5-30) days after infarction using a limited Naughton protocol. Thirty five (34%) of the patients had had reciprocal change, defined as greater than or equal to 1 mm ST depression in leads remote from the site of the infarct, within 48 hours of infarction. Twenty two (63%) of the 35 patients developed exercise induced ST depression in the leads previously showing reciprocal change. Coronary artery disease was assessed in 10 of these patients by arteriography and in four at necropsy: all but one had stenosis of greater than or equal to 50% in a coronary artery supplying the reciprocal territory in addition to the disease in the vessel to the infarct site. Of patients with reciprocal ST depression, 23.5% experienced nonfatal reinfarction, pulmonary oedema after discharge, or death compared with only 9.5% of patients without reciprocal ST depression. Eight (23.5%) patients with reciprocal depression had ventricular fibrillation while in hospital compared with only two (3%) patients without. Reciprocal ST depression in acute myocardial infarction may reflect ischaemia in territory distant from the site of infarction and is associated with a high risk of fatal arrhythmias and late morbidity.